Successful Outcome of Triangle Tilt as Revision Surgery in a Pediatric Obstetric Brachial Plexus Patient with Multiple Previous Operations - Rahul K. Nath; Vishnu Halthore; Chandra Somasundaram (Case Reports in Surgery)
Introduction. Obstetric brachial plexus injury (OBPI) occurs during the process of labor and childbirth. OBPI has been reported to be associated with shoulder dystocia, macrosomia, and breech delivery. Its occurrence in uncomplicated delivery is possible as well. Case Presentation. The patient in the present report is a 6.5-year-old girl, who suffered a severe brachial plexus injury at birth and had many reconstructive surgical procedures at an outside brachial plexus center before presenting to us. Discussion. The traditional surgical treatments by other surgical groups were unsuccessful and therefore the patient came to our clinic for further treatment. She had triangle tilt surgery with us, as a salvage procedure. Conclusion. The OBPI patient in this study clearly showed noticeable clinical and functional improvements after triangle tilt surgical management. The posture of the arm at rest was greatly improved to a more normal position, and hand to mouth movement was improved as well. Triangle tilt surgery should be conducted as a first choice treatment for medial rotation contracture of the shoulder in OBPI patients.